Relationship between vitamin A and ?-carotene levels during the postpartum period and fertility parameters in cows with and without retained placenta - Akar, Y; Gazioglu, A (Natl Veterinary Research Inst, 2006)
Serum vitamin A and beta-carotene levels were ascertained in cows with and without retained placenta during 2-6 weeks postpartum and their relationship to fertility parameters were studied. Twenty cows with retained placenta and 20 controls were examined. In cows with retained placenta, serum vitamin A values were significantly lower in the 2 Id week after parturition when compared with the other weeks. In the control group, the values were significantly higher the 6(th) week than those in the 2(nd) and 4(th) weeks. Serum vitamin A level in the retained placenta group was significantly lower than that in the control group in the 3(rd), 5(th) and 6(th) weeks. Serum beta-carotene levels increased gradually in both groups after parturition. Values for the retained placenta cows were significantly lower than in the controls throughout the postpartum period. The calving to the first oestrus and calving to conception intervals were considerably longer in the retained placenta group, but statistically no significant differences were found between the groups in terms of calving to conception interval, services per conception, the first service conception rate, and total pregnancy rate. It was concluded that poor fertility parameters in cows with retained placenta, as compared to the control group, could relate to the low content of vitamin A and especially beta-carotene.
Keywords: cow; retained placenta; vitamin A; beta-carotene; fertility